Geographies of identity in nineteenth-century Japan - Howell, David L. (Berkeley, Calif. : University of California Press, 2005)
In this pioneering study, David L. Howell looks beneath the surface structures of the Japanese state to reveal the mechanism by which markers of polity, status, and civilization came together over the divide of the Meiji Restoration of 1868. Howell illustrates how a short roster of malleable, explicitly superficial customs--hairstyle, clothing, and personal names-- served to distinguish the "civilized" realm of the Japanese from the "barbarian" realm of the Ainu in the Tokugawa era. Within the core polity, moreover, these same customs distinguished members of different social status groups fro
The geography of status -- Status and the politics of the quotidian -- Violence and the abolition of outcaste status -- Ainu identity and the early modern state -- The geography of civilization -- Civilization and enlightenment -- Ainu identity and the Meiji State.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Japan -- Civilization -- 19th century; Japan -- Social conditions -- 19th century; Ainu -- Ethnic identity; Aïnou (Peuple d'Asie) -- Identité ethnique; Japon -- Civilisation -- 19e siècle.; Japon -- Conditions sociales -- 19e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; HISTORY -- Asia -- General; Ainu -- Ethnic identity; Civilization; Social conditions; Japan; Ethnische Identität; Sozialstatus; Japan; Ainu; 1800-1899; ainu culture; ainu; anthropology; assimilation; barbarian; barbarism; bunka; buraku; burakumin; burakushi; civilization; class; commoner; cultural difference; custom; daimyo; early modern japan; east asia; folk practices; folk tradition; history; japan; japanese history; meiji restoration; nation; national identity; nonfiction; othering; outcast; peasant; polity; race; samurai; social status; status; tokugawa